Pengembangan Media Video Animasi Pembelajaran Untuk Meningkatkan Kemampuan Berbahasa Anak Usia Dini - Mutiara Aminah (Indonesian Journal of Elementary School, 2023)
Early childhood learning needs for visual media with multimedia facilities are less attention and development. This results in the emergence of obstacles in increasing the development of children's abilities and potentials. This study aims to define the learning needs of early childhood, develop learning animation videos, and determine the role of using learning animation videos in improving children's language skills. The development approach taken is to use the Thiagarajan model, namely definition, design, and development. From the results of the analysis carried out after the children were given learning through animated videos, there was an increase in aspects of understanding language, aspects of expressing language, and literacy. In the end, this research can prove that audio-visual media using animated videos plays a role in improving early childhood language skills, so it needs to be developed so that learning activities are more varied and innovative. Keywords: Animation Video, Language Skills, Early Childhood.